Compatibility of Cymbopogon citratus (DC.) Stapf (Poaceae) essential oil with egg parasitoids for the control of Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) - de Andrade Bomfim, João Pedro [UNESP]; da Silva, Nadja Nara Pereira [UNESP]; da Silva, Carolane Benjamin [UNESP]; Amaral, Jéssica Cristina; das Graças Fernandes da Silva, Maria Fátima; Bonfim, Filipe Pereira Giardini [UNESP]; de Oliveira, Regiane Cristina [UNESP] (Springer Nature, 2025)
Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is an insect pest of global importance, and the search for phytosanitary products with less impact on the environment and human health has intensified. This study aimed to determine the chemical profile of Cymbopogon citratus (DC.) Stapf (Poaceae) essential oil (EO) and its potential to control S. frugiperda and its selectivity for the natural enemies Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) and Telenomus remus Nixon (Hymenoptera: Scelionidae) were evaluated. C. citratus leaves were collected and dried, and the oil was extracted via a Clevenger-type apparatus. Gas chromatography coupled with mass spectrometry was performed to identify and quantify the compounds in the EO. The experiments were carried out by adding C. citratus EO at different concentrations: 0.00, 0.50, 0.75, 1.25, 1.50, 1.75, 2.00, 2.75, and 3.00 mg of oil/g of artificial diet. An experiment was conducted with concentrations corresponding to the LC80. The effects of fumigation at different concentrations on natural enemies were tested. Geranial and neral are the major components of EO. The applied concentrations of EO were toxic to S. frugiperda larvae, with LC50 = 2.016, LC80 = 2.577, and LC95 = 3.257 (mg/g), and citral caused mortality above 90%. The EO caused greater mortality in T. pretiosum (94.0–100.0%) than in T. remus (12.0–38.0%). In conclusion, C. citratus EO effectively reduced S. frugiperda populations, but the staggered application is recommended to minimize the impact on parasitoids, enhancing ecological selectivity.
Keywords: Biological control; Botanical insecticides; Egg parasitoids; Fall armyworm; Integrated pest management